Analysis of performance for the Japan men's water polo team in the World Championships by factor analysis - Factors on the improvement of the team performance - Suga, M.; Enomoto, I.; Takagi, H. (Japanese Journal of Sciences in Swimming and Water Exercise, 2006)
The purposes of this study are to extract factors which compose a water polo team's performance and to determine the factors on the improvement of the Japanese men's water polo team. The posted results of 156 water polo games from 2001, 2003 and 2005 World Championships are analyzed. Factor analysis was carried out on various data including: the shots classified by attack patterns, the exclusions, the saves by goal keeper and the defense in 156 games which were released to web site. As a result, there exist seven factors representing dimensions of team performance. They are named as follows: "F1: defense ability in extra-man situations" "F2: counter attack shot ability" "F3: ability of center forward to force defender exclusions" "F4: ability of center forward to get shots off" "F5: outside shooting and drive shooting ability" "F6: ability of field players to force exclusions" "F7: saving ability of goal keeper" The analysis of these factors suggested that the improvement of Japan's team performance from 2001 to 2005 was a result of the center forward and goal keeper ability (F3 and F7) and the extra-man offense ability (F3) improving to a high level world standard.